The Inventory Management Process Improvement of Raw Materials in Food and Beverage Industry : A Case Study of ABC Company Limited - สินวัฒนาเกษม ชุติมา; คำสุข แววมยุรา (Business Administration and Management Journal Review, 2013)
This independent study is aim to analyze the causes of inventory management of raw materials in food and beverage industry, to improve efficiency and process of inventory management including to reduce costs and expense in managing inventory. The theory of ABC Classification System determined the priority of each product. To find the products that were vital for class A in this study, an analysis of available products with priority A in total of 32 items were identified by the new inventory management processes. The response to the information provided customer’s information and control of an order to the appropriate level. Along with the application of theory to aid in the MRP (Material Requirements Planning) in SAP system, this serves to calculate the amount and timing of orders, pending delivery and transit time. All were considered for the most appropriated needs. The results of this study revealed that after the company improved inventory management with the above 32 transaction’s products. This can reduce inventory holding cost to 41.7 million baht from 71.8 million baht or the reduction of inventory holding cost to 30.1 million baht or 41.9% of the inventory holding cost of total 32 items.